포푸라와 일본잎갈나무의 집성재 제조에 관한 연구 - 조재명; 강선구; 김기현; 정병재; Jae Myeong Jo; Sun Goo Kang; Ki Hyeon Kim; Byeong Jae Chung (목재공학, 1974)
1. Various gluing qualities applying Resorcinol Plyophen #6000 were studied on aiming the strength relationships of laminated woods resulted by single species [poplar (Populus deltoides), larch(Larix leptolepis)], mixed species of (poplar and larch), preservatives, treated poplar the scarf joint with mixed species of poplar and larch and the scarf joint treated with preservatives. 1. 1 On the block shear and on the DVL tension test, the mean wood failure ratio showed an excellent value i.e., above 65% and the tangential strength for larch was higher than that of radial, but it was reversed for poplar as shown in Tables 1 and 2. 1. 2 The lamina treated with Na-PCP reduced slightly the strength but the limited strength allowed for manufacturing laminated wood was not influenced by treating Na-PCP as shown in Tables 3 and 4. 1. 3 The safe scarf ratio in the plane scarf joint was above 1/12 for larch and 1/6 for poplar regard less of the chemical treatment or untreatment as shown in Tables. 5, 6, 7 and 8. 2. In the normal and boiled state, the gluing quality of the laminated wood composed of single[poplar (Populus deltoides), larch (Larix leptolepis)] and double species (poplar and larch) glued with Resorcinol Plyophen #6000 were measured as follow, and also represented the delamination of the same laminated wood. 2.1 The normal block shear strength of the straight and curved laminated wood (in life size) were more than three times of the standards adhesion strength. And, the value of the boiled stock was decreased to one half of the standard shear adhesion strength, but it was more than twice the standard strength for the boiled stock. Thus, it was recognized that the water resistance of the Resorcinol Plyophen #6000 was very high as shown in Tables 9 and 10. 2. 2 The delamination ratio of the straight and curved laminated woods in respect of their composition were decraesed, in turn, in the following order i. e., larch, mixed stock (larch+poplar) and poplar. The maximum value represented by the larch was 3.5% but it was below the limited value as shown in Table 11. 3. The various strengthes i.e., compressive, bending and adhesion obtainted by the straight laminaced wood which were constructed by five plies of single and double species of lamina i. e., larch (Larix leptolepis) and poplar (Populus euramericana), glued with urea resin were shown as follows: 3. 1 If desired a higher strength of architectural laminated wood composed of poplar (P) and larch (L), the combination of the laminas should be arranged as follows, L+P+L+P+L as shown in Table 12. 3.2 The strength of laminated wood composed of laminas which included pith and knots was conside rably decreased than that of clear lamina as shown Table 13. 3.3 The shear strength of the FPL block of the straight laminated wood constructed by the same species which were glued with urea adhesives was more than twice the limited adhesion strength, thus it makes possible to use it for interior constructional stock. 포푸라와 일본잎갈나무는 속성조림 수종으로 적극 장려되고 있으나 구조용재로서 저재질인 까닭에 그 이용도가 제한되고 있다. 따라서 이들의 이용도 증진과 수요의 안정화를 위하여 대량으로 소비되는 일반 건축용재로 이용할 수 있는 형질의 개량과 강도 증진을 목적으로 임업시험장에서 1967년부터 포푸라와 일본잎갈나무의 집성재 제조조건을 구명하기 위하여 본 시험연구를 시작하여 현재까지 포푸라와 일본잎갈나무의 접착, scarf 접착성능과 실대형통직, 만곡 집성재의 제조조건 및 이 수종 구성집성재 제조에 의한 포푸라재의 집성강도 증진과 lamina 형질이 집성 강도에 마치는 영향을 구명한 결과 다음과 같은 결론을 얻었다. 1. 접착제 Resorcinol Plyophen #6000에 의한 미류(Populus deltoides)와 일본잎갈나무(Larix leptolepis)의 단일 수종, 이수종 접착성능, 방부처리, 미류의 접착성능과 미류와 일본잎갈나무의 scarf 접속 정착성능 및 방부처리, 마류의 scarf 접착성능을 구명한 결과 1.1 Block 전단 및 안장선단 시험에 의한 접착성능은 평균 목파율이 65%로 우수하였고, 미류는 촉단면이 경단면보다, 일본잎갈나무는 경단면이 촉단면 보다 접착성이 양호하였다(표 1, 2참조). 1. 2 방부제 Na-PCP는 resorcinol 수지 접착제의 접착력에 영향 하였으나 집성재 제조에 요구되는 접착력에는 영향하지 않았다(표 3, 4참조). 1. 3 Plane scarf joint 접착에 있어서 안전한 scarf비는 일본잎갈나무 1/12이상, 미류는 1/6이상이 요구되고 방부처리 미류의 plane scarf joint 접착의 안전 scarf 비도 무처리재와 같이 1/6 이상이 요구되었다(표 5, 6, 7 및 8참조). 2. 접착제 Resorcinol Plyophen #6000에 의한 미류와 일본잎갈나무의 단일 수종 및 이수종구성 집성재의 상대 접착력과 삶음반복 접착력 및 접착층의 박리시험에 의한 접착성능을 구명한 결과 2.1 실대형 통직, 만곡 집성재의 block 전단 상태 접착강도는 허용 최소상태 접착강도의 3배 이상이였으며 삶음반복 접착 강도는 상태접착 강도의 1/2로 감소 되었으나, 허용 최소 기준 삶음반복 접착강도의 2배 이상으로 실대형 내수 집성재 제조의 안전성이 확인되였다(표 9 및 10참조). 2.2 실대형 통직, 만곡집성재의 박리율은 미류, 이수종(일본잎갈나무+미류), 일본잎갈나무의 순으로 높았으나 최대치는 일본잎갈나무의 통직집성재(3.5%)로서 허용 최대 기준율보다 적었다.(표 11 참조) 3. urea 수지 접착제에 의한 이태리포푸라(Populus euramericana)와 일본잎갈나무의 단수종, 이수종 및 lamina 형질에 따른 5 ply 구성 통직 접성재의 휨강도 시험, 압축강도 시험에 의한 집성강도와 접착성능을 구명한 결과 3.1 집성강도가 요구되는 건축 구조용재를 목적으로 이태리포푸라와 일본잎갈나무의 이수종 구성 집성재를 제조할 때에는 수종 구성을 L(일본잎갈나무)+P(이태리포푸라)+L+P+L로 하는 것이 양호하였다.(표 12참조) 3.2 수심과 옹이를 가지는 lamina로 구성된 집성재의 경성 강도는 무결점 lamina로 구성된 집성재 강도보다 현저히 강도가 감소되므로 강도가 요구되는 구조용재로서의 집성재 제조에는 이들 결점 부재의 분산 집성이 필요하였다.(표 13참조) 3.3 실대형 통직 집성재의 FPL 전단 상태 접착강도는 허용 최소기준 상태 접착강도의 2배 이상으로 urea 수지접착제로서 이을 수종의 내장주조용 집성재 제조가 가능하였다.